Pengelolaan Perpustakaan Masjid Berdasarkan Keputusan Direktur Jendral Bimbingan Masyarakat Islam Nomor 543 Tahun 2019 di Perpustakaan Masjid Al-Markaz Al-Islami Makassar - Nasrullah Nasrullah; Fatri Ardiansyah; Andi Khaerun Nisa; Ismaya Ismaya (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2022)
This study aims to determine the implementation and the obstacles in implementing the mosque library management guidelines based on the Decree of the Director General of Islamic Community Guidance Number 543 of 2019 at the Al Markaz Al Islami Makassar mosque library. This research is descriptive with a qualitative approach. Data collection techniques were carried out by observation, interviews and documentation. Data processing and analysis techniques were carried out through three stages: data reduction, data presentation and conclusion. The results of the study show that the implementation of the Director General of Islamic Community Guidance Decree Number 543 of 2019 regarding guidelines for managing mosque libraries in the Al Markaz Al Islami Makassar mosque library has mainly been implemented. It's just that there are still guidelines that cannot be implemented, namely the guidelines for library financing, collaboration and promotion. The obstacles to implementing the Decree of the Director General of Islamic Community Guidance Number 543 of 2019 in the management of the Al Markaz Al Islami Makassar mosque library were the lack of human resources, library promotion has not been maximized, lack of budget support from the Foundation, and technological facilities are often disrupted